Health and Well-Being of Young People : A Multi-Sectoral Approach to Operational Planning - Saadat, Seemeen (World Bank, Washington, DC, 2017)
This note discusses avenues for multi-sectoral approaches and strategies to address adolescent and youth health. Successful application of any multi-sectoral approach requires strong and continuous partnerships with different stakeholders including within the Bank. It requires building effective multi-sectoral teams with dedicated resources that can build bridges across different sectors within the Bank and at the country level. While opportunities for collaboration depend on country contexts, keeping adolescents and youth at the center of an intervention will help align and define multi-sectoral actions across different areas. For more information on this topic, go to: www.worldbank.org/health.